STRATEGI PENINGKATAN KINERJA PELAYANAN PERUMDA AIR MINUM TIRTA SENENTANG MELALUI ANALISIS SWOT - Kubu, Thomas; Ulfah, Maria; Kuswanti, Heni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2025)
This study examines strategies to improve service performance at the Tirta Senentang Drinking Water Company (PERUMDA) using a descriptive qualitative approach. Data were collected through observation, interviews, and documentation with six informants: three employees and three customers from different distribution points. The findings show that PERUMDA has implemented strategies such as enhancing raw water processing, refining production, extending operating hours, expanding service access through government support, and strengthening customer complaint handling. These efforts resulted in better service, demonstrated by a 100% resolution of complaints, 83.3% water quality achievement, and a minimum of 18 hours daily supply. Strengths include leadership commitment, local government support, and clear service SOPs, while weaknesses involve customer appreciation and dependence on water sources. Opportunities arise from government programs and public awareness, while threats relate to environmental issues and fluctuating customer numbers. In conclusion, through SWOT analysis, the company develops strategies that maximize strengths and opportunities while reducing weaknesses and threats to ensure sustainable service performance.